2015
DOI: 10.1016/j.jhin.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cleaning and disinfection of toys on infectious diseases and micro-organisms in daycare nurseries

Abstract: Although cleaning and disinfection of toys every two weeks can decrease the microbial load in nurseries, it does not appear to reduce sickness absence among nursery children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 24 publications
3
46
0
Order By: Relevance
“…Although we identify some research on the hygiene of toys in health settings [6,16], the study of their use related to teaching and learning also needs special attention, since it is known that day care centers are considered important sites for direct transmission and indirect use of infectious microorganisms [4,[10][11][12][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we identify some research on the hygiene of toys in health settings [6,16], the study of their use related to teaching and learning also needs special attention, since it is known that day care centers are considered important sites for direct transmission and indirect use of infectious microorganisms [4,[10][11][12][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on bacteriological conditions and their pathogenic potential in toys and in the hands of children in the hospital and outpatient settings highlight the importance of choosing the appropriate product for cleaning and disinfection [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is certainly a limitation of this study, as studies modeling the behavior of expiratory aerosols show that ventilation rate has a lower significance on indirect contact transmission than it does on the airborne transmission (Wan et al., ). This paper is not focused on the relationship between sick leave among children and presence of bacteria and virus; this issue will be discussed elsewhere (Ibfelt et al., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the isolated bacteria in these environments are low in pathogens, a study on daycare environments showed positive culture results in 60% of the samples. Toys are among the fomites with the highest pathogen agent load, for which reason various strategies have been studied to reduce microorganism loads on these surfaces (3) . An effective measure for preventing infection is hand hygiene.…”
Section: Introductionmentioning
confidence: 99%